I Centri per l’impiego nei nuovi orientamenti delle politiche attive per il lavoro: vincoli o risorse? - Avola, Maurizio; Azzolina, Laura; Cuttone, Marco (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
In line with recent labour policy reforms, as well as the European programme known as Youth Guarantee, in Italy public employment services have gained a new centrality in active labour policies. However, public employment services in Italy have been only partially modernised and many critical issues still persist. As a result, a debate on the capacity of employment services to play efficiently an active role in labour policies supply has developed. This paper analyses employment centres in 4 areas in Sicily (one of the weakest regions in Italy in terms of institutional efficiency on labour policies), and their performance in the implementation of Youth Guarantee. The work shows the organizational change, the improved relational capacity and the institutional growth following this experience.